Analysis of fruit and vegetable consumption by different population groups - Z. N. Khatko; E. M. Kolodina (Новые технологии, 2019)
The article presents the results of the conducted questionnaire on the food ration of the 18-90 year old population of the Republic of Adygeya (Maikop) and the Krasnodar Territory (Labinsk). The physiological data of the respondents are given and their body mass indices have been calculated. Different age groups of the population are considered, and also annual physiological norms of consumption of the studied groups of products are given. To assess the frequency and quantity of food consumption a survey has been conducted. The results of the survey are presented in the form of diagrams of the frequency of consumption of these groups of products according to the method developed by the Sports Nutrition Laboratory with a group of nutritional pathology of the Research Institute of Nutrition of the RAM. Estimation of the amount of consumed fruits and vegetables has been carried out by calculating the average daily consumption, the obtained data have been analyzed for compliance with physiological norms of consumption. Individual values of the periodicity of consumption have been established, as well as common features and differences in rations for the studied groups of respondents have been identified. The values of the maximum and minimum daily consumption of these types of products (fruits and vegetables) are given; summary tables have been compiled on their basis and the average daily consumption rates of products for the respondents of these age groups have been calculated.